Kokoza A. A. Сommunicative strategies and tactics of personalization of the newspaper discourse via the means of the lexemes of clothes nominations - Kokoza A. A. (Philological Treatises, 2020)
The article aims at outlining communicative strategies and tactics of personalization of the newspaper discourse via the means of the lexemes of clothes nominations. The identified strategies facilitate the formation of inclusive, cooperate relations between the addresser and addressee by presenting a persona, who is the subject- matter of the discourse fragment, as a member of a certain social group (age, nationality, social status, profession) targeted to propel feelings of solidarity and affiliation between her and addressee. Conformity to social expectations evokes positive feelings of the general public towards a famous persona and therefore serves to enhance her positive image (strategy of the positive image creation of a public person), while the frustration of the social code of conduct contributes to the destruction of the positive image.